Bis(tetramethylaluminate) complexes of yttrium and lanthanum supported by a quinolyl-substituted cyclopentadienyl ligand: synthesis and performance in isoprene polymerization - Litlabø, Rannveig; Enders, Markus; Törnroos, Karl W.; Anwander, Reiner (Organometallics, 2010)
Quinolyl-substituted half-sandwich complexes (CpQ)Ln(AlMe4)2 (CpQ = 2,3,4,5-tetramethyl-1-(8-quinolyl)cyclopentadienyl; Ln = Y, La) were obtained in quantitative yield via protonolysis reactions utilizing HCpQ and homoleptic tetramethylaluminates Ln(AlMe4)3. X-ray structure analyses revealed that the quinolyl-substituted cyclopentadienyl ligand coordinates to the rare-earth metal centers in an η5:η1 fashion through the Cp ring carbon atoms and the N atom of the quinolyl substituent. The complexes (CpQ)Ln(AlMe4)2 show good activity and high trans-1,4-stereoselectivity (maximum 93%) in the polymerization of isoprene upon activation with the organoborates [Ph3C][B(C6F5)4] and [PhNMe2H][B(C6F5)4]. The effects of metal size, cocatalyst, temperature, and solvent were assessed in these polymerization reactions, and the performance of such N-donor-functionalized complexes was compared to that of (CpR)Ln(AlMe4)2 containing different types of nondonor-functionalized cyclopentadienyl ligands.